Peran Teknologi dalam Layanan Komunikasi Koperasi di Era Digital - Farida Farida; Irfan Rofiq (J-Coop : Journal of Co-operative, 2025)
Digital transformation in cooperative services has become urgent in the technology-driven economy. This study aims to describe the process of digital communication transformation in cooperative services and provide strategic recommendations for optimizing technology-based services to enhance cooperative service efficiency. The research employs a qualitative descriptive approach using observation, interviews, and literature review methods. Koperasi Tawakal Kreasi Indonesia (KTKI) was selected as the case study because this savings and loan cooperative has been developing the KITA application as a digital solution to improve cooperative services for its members, particularly online motorcycle taxi driver communities. The findings reveal that the managerial functions—planning, organizing, actuating, and controlling— play a crucial role in the success of digital transformation in cooperatives. Information technology has been proven to enhance service accessibility, transparency, and operational efficiency. However, implementation challenges include human resource limitations, resistance to change, and administrative obstacles. This study recommends several strategies, including enhancing the capacity of the information technology team, conducting member outreach and education, optimizing digital infrastructure, resolving cooperative governance issues, and strengthening strategic partnerships. By implementing these strategies, digital transformation is expected to increase cooperative competitiveness, expand service reach, and sustainably improve member welfare.